THE UTILIZATION OF HOUSEHOLD WASTE THROUGH ECOENZYMES - Ade Ihtiar; Titis Dewi Vira, Lilla Panca Faizsyahrani, Novita Anggraini, Vionika Azuhro, Endah Rita Sulistya Dew (International Journal Of Humanities, Social Sciences And Business (INJOSS), 2023)
The existence of household waste has a huge impact on the environment and health if left unchecked. One way to process household waste into useful products is by making Ecoenzyme. This study aims to determine the utilization of household waste through ecoenzyme by analyzing the literature review. There are 14 scientific articles used in this research which come from 12 accredited national journals and 2 journal proceedings articles. The technique of presenting the data is using a table listing scientific publication articles that will be analyzed into research data. Data analysis techniques were carried out descriptively by analyzing and identifying scientific articles so as to produce a more formative summary. The results of the literature review research show that this Ecoenzyme is an alternative to organic waste processing, especially in household waste, this Ecoenzyme has  several product results and their uses. In agriculture, Ecoenzyme is used as liquid organic fertilizer (POC). The results of Ecoenzyme are also used as cleaners, soaps, hand sanitizers, disinfectants, and are made in the form of essential oils to be added to water purifiers.